Chronic obstructive pulmonary disease: aetiology, pathology, physiology and outcome. (May 2020) - Cheng, Daryl; Hurst, John R.
Abstract: Chronic obstructive pulmonary disease (COPD) is a physiological diagnosis made on the basis of airflow obstruction. It develops when a genetically susceptible individual encounters sufficient inhaled environmental triggers. Genetic susceptibility is complex and determined by multiple alleles, with emphysema from α1 -antitrypsin deficiency being a rare exception of well-described genetic risk. Cigarette smoke is the most common trigger in higher income countries, but globally the burning of biomass fuel in underventilated spaces is an important contributor to COPD. The natural history of lung function decline and maximal lung function attainment is fundamental to understanding COPD and still incompletely understood. In individuals susceptible to the effects of smoke, the airway inflammatory response is qualitatively and quantitatively different from that in non-susceptible individuals. Once established, inflammation persists even after exposure to smoke has ceased. Airflow obstruction in COPD results from a combination of airway wall inflammatory response, luminal mucus accumulation and loss of alveolar–airway attachments from emphysema. The major symptoms of COPD are breathlessness, cough and sputum expectoration. Breathlessness is casually multifactorial, with a contribution from dynamic hyperinflation. Although progressive airflow obstruction is the hallmark of COPD, it is recognized that other outcomes are also important, notably exacerbations and the development of co-morbidities.